Bioekologi Bulu Babi (Echinoidea) pada Ekosistem Padang Lamun Di Kecamatan Kupang Barat - Fransiska Reni Klau; Subagiyo Subagiyo; Ita Riniatsih (Jurnal Kelautan Tropis, 2025)
Sea urchins (Echinoidea) are one of the marine biota found in seagrass ecosystems in West Kupang District, East Nusa Tenggara. Sea urchins have an important role in the food chain cycle in seagrass ecosystems and are known as healthy food due to their high nutritional content. Sea urchin gonads contain protein, fat, vitamins and essential fatty acids, which are beneficial for human health. In addition to economic value, sea urchins also have ecological value in balancing and controlling macroalgae in coral reef and seagrass ecosystems. The aim of this research is to determine the bioecology of sea urchins in four research locations, namely Bolok, Lalendo, Baliana, and Tablolong beaches. The research method used was direct observation with Megabenthos and Benthos Belt Transect (BBT) techniques. The results showed that there were five types of sea urchins in the study site, namely Diadema setosum, Tripneustes gratilla, Echinometra calamaris, Echinothrix diadema, and Echinometra mathaei.   The results showed that the abundance of Diadema setosum individuals on Tablolong beach (0.46 ind/m²) while Tripneustes gratilla was dominant on Baliana beach (0.22 ind/m²). The highest species diversity index (D) was found in Lalendo (0,7) and the lowest in Tablolong (0,5), indicating moderate diversity. The uniformity index (E) was highest in Baliana (0.8) indicating a more even distribution of species than Tablolong (0.6), the dominance index (C) was highest in Lalendo (1.0), indicating a strong dominance of species at the site.   The highest Index of Gonadal Maturity (IKG) value for Diadema setosum was found in Tablolong (26.9), while Echinometra mathaei in Lalendo (68.6). The food consumption pattern of sea urchins showed that Tripneustes gratilla consumed more seagrass, especially at Baliana beach (82,08%), while Echinothrix diadema predominantly consumed seagrass at Lalendo and Baliana beaches.